Identification and genomic comparison of temperate bacteriophages derived from emetic Bacillus cereus. - Peiling Geng; Shen Tian; Zhiming Yuan; Xiaomin Hu (PLoS ONE)
Cereulide-producing Bacillus cereus isolates can cause serious emetic (vomiting) syndrome and even acute lethality. As mobile genetic elements, the exploration of prophages derived from emetic B. cereus isolates will help in our understanding of the genetic diversity and evolution of these pathogens. In this study, five temperate phages derived from cereulide-producing B. cereus strains were induced, with four of them undergoing genomic sequencing. Sequencing revealed that they all belong to the Siphoviridae family, but presented in different forms in their hosts. PfNC7401 and PfIS075 have typical icosahedral heads, probably existing alone as phagemids in the host with self-replicating capability in the lysogenic state. PfEFR-4, PfEFR-5, and PfATCC7953 have elongated heads, with the genomes of the former two identified as linear dsDNA, which could be integrated into the host genome during the lysogenic state. Genomic comparison of the four phages with others also derived from emetic B. cereus isolates showed similar genome structures and core genes, thus displaying host spectrum specificity. In addition, phylogenic analysis based on the complete genome and conserved tail fiber proteins of 36 Bacillus species-derived phages confirmed that the phages derived from emetic B. cereus strains were highly similar. Furthermore, one endolysin LysPfEFR-4 was cloned and showed lytic activity against all tested emetic B. cereus strains and cross-lytic activity against some other pathogenic bacteria, implying a potential to control bacterial contamination in the food supply.